Nutritive value and fatty acids profile of fresh Indonesian eel (Anguilla bicolor) and kabayaki - Clara M. Kusharto; R.A. Hangesti Emi Widyasari; Budywiryawan; Eko Sri Wiyono; Sugengherisuseno (penerbit ukm, 2014)
Eel were known asa food source that contain high nutrients. Recently, the utilization of Eel for export purposes has remained high. The aim of this study were to analyze the nutritive value and fatty acids profile of fresh Indonesian eel and roasted eel (kabayaki). This study were conducted at P.T. Jawa Suisan Indah, Sukabumi District, West Java Province, and Kimia Terpadu Laboratorium Bogor Agricultural University, from October 2012 to May 2013. The proximate analysis on fresh Indonesian Eel showed that it contained 17.68% of protein, 28.29% of fat, 42.03% of moisture, 3.93% of ash and 0.30% of crude fiber. While Kabayaki contains 32.70% of protein, 2.39% of fat, 48.32% of moisture, 2.37% of ash and 0.55% of crude fibre. The fatty acids composition of fresh Indonesian Eel consisted of 22.78% saturated fatty acids (SFA), 32.84% monounsaturated fatty acids (MUFA), 11.4% polyunsaturated fatty acids (PUFA), 1.15% eicosapentaenoic acid (EPA) and 5.16% docosahexaenoic acid (DHA). While kabayaki contained 30.68% SFA; 31.1% MUFA; 10.39% PUFA; 0.70% EPA and 1.29% DHA.